Karakteristik Aspal Buton Ekstraksi yang Dimodifikasi dengan Oli Bekas dan Plastik HDPE - I.D.M.A. Karyawan; N.N. Kencanawati; H. Hariyadi; H. Hasyim; R. Rohani (Civil Engineering Department, Tadulako University, 2023)
Asphalt functions as an aggregate binder in the road pavement mixture. The rapid construction of roads causes the need for asphalt to increase, while its availability is limited. The government is promoting the use of natural asphalt (Asbuton) as an alternative to oil asphalt. However, asphalt performance from Asbuton is not good. Uneven asphalt content and Asbuton hardness are factors causing it to be less effective as a binder. It is necessary to improve performance by modifying the bitumen separated from Asbuton granules by the extraction process. The modifications were made using used oil and high-density polyethylene (HDPE) plastic waste. Samples were made for each variation of used oil and HDPE in two ways: a constant 5% used oil composition and a constant 2% HDPE. In the constant 5% oil variation, 0%, 2%, 4%, and 6% HDPE are used. Whereas at a constant 2% HDPE, 0%, 3%, 5%, and 7% used oil are used. The tests carried out were: 1) Moisture content and ash content of asphalt extracted from Asbuton, 2) Penetration of asphalt, 3) Ductility; 4) Loss of weight, 5) specific gravity, 6) softening point, and 7) flash and burn points. The performance of modified asphalt is known from the results of data analysis from the tests carried out. The results of the analysis showed that in the asphalt weight loss test, specific gravity, and softening point, pure Asbuton extraction asphalt and the results of the modification as a whole met the requirements. However, in the penetration test, only 3 variations met the requirements, namely: 5% and 7% used oil, and 2% and 6% HDPE. Whereas in the ductility test, flash point, and burning point, all variations and asphalt extraction of pure Asbuton did not meet the requirements. Low ductility, meaning that asphalt does not have good cohesive properties. The low flash point and burning point indicate that the asphalt is easy and fast to burn, which affects the mixing process. Thus, it is still necessary to optimize the composition of the modifier so that the requirements for ductility, flash point, and firing point are met.